2007
DOI: 10.1530/rep-07-0220
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of bovine epididymal activity by oxytocin and noradrenaline

Abstract: Passage of spermatozoa through the epididymis and emission of sperm during ejaculation are based on spontaneous and induced contractions of epididymal peritubular muscle layers. This study deals with the ejaculation-relevant factors noradrenaline (NA) and oxytocin (OT) and their contractile effects in the course of the bovine epididymal duct. Muscle tension recording revealed excitatory effects of NA in all duct regions. A peculiarity was found in a duct section between the mid-cauda and ductus deferens, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 47 publications
(63 reference statements)
1
11
0
Order By: Relevance
“…As suggested before for different species [16], [24], [25], [27], [28] we observed a regular and phasic contractile activity in duct segments of all parts investigated in the caput and corpus regions. Direct information on contractile force, however, cannot be deduced directly by our experiments.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As suggested before for different species [16], [24], [25], [27], [28] we observed a regular and phasic contractile activity in duct segments of all parts investigated in the caput and corpus regions. Direct information on contractile force, however, cannot be deduced directly by our experiments.…”
Section: Discussionsupporting
confidence: 87%
“…This was neither possible by previously used visual studies [3], [24] nor by pure physiological settings [15], [16], [25], [26] and it was interesting to see that the frequency of spontaneous contractions remained stable over the length of one isolated part of the epididymal duct.…”
Section: Discussionmentioning
confidence: 93%
“…OT (500 nM), which was recently found to evoke strong contraction in the epididymal cauda region (24), was applied at the end of each experiment to check intactness of the epididymal musculature. To test the ability of E-4031 to affect contraction in the cauda (m), the channel blocker was applied after application of OT (500 nM).…”
Section: Effects Of E-4031 and Ns-1643 On Epididymal Contractilitymentioning
confidence: 99%
“…A relaxing effect was noted in cow corpus and proximal cauda epididymidis. 22 One study found no electrical or mechanical effects of oxytocin on rat caput or cauda epididymidis. 27 In rat and rabbit epididymis (without specifying which part exactly) another study reported oxytocin to have no effect 28 but found vasopressin (which differs to oxytocin only by two amino acids) to have an increasing effect, suggesting that the vasopressin 1 A receptor rather than the oxytocin receptor might be involved in signal transduction of oxytocin in the epididymis.…”
Section: Introductionmentioning
confidence: 99%